Developmental Changes in Active Learning of Transitive Relations. - Markant, Douglas B.; Battisti, Antonella; Ruggeri, Azzurra (Developmental Psychology, 2026)
Combining memories of related experiences is fundamental to the formation of generalizable knowledge. Past work has shown that the ability to integrate and reason about related events improves across childhood. However, little work has examined developmental changes in the ability to actively construct new relational knowledge by making decisions about how to study related materials. We used a transitive inference (TI) task to examine the active construction of relational knowledge in 7- to 17-year-old children (N = 107). We find that age-related improvements in relational inference are accompanied by an increasing preference for "chained" study, such that overlapping relations are studied in consecutive trials. Using computational models of transitive inference, we show that these developmental changes are consistent with a growing tendency to link individual relations together into a single mental structure while learning. This process is facilitated when children study premises in chained sequences. These findings suggest that exploratory study behaviors that promote relational reasoning emerge late in childhood, developing alongside the capacity to maintain and manipulate more complex mental representations. Public Significance Statement: Effective learning is not just about memorizing facts, but often requires linking ideas into generalizable knowledge. By examining how children choose to study related ideas in a transitive inference task, this study shows that older children increasingly adopt strategies that help them integrate separate experiences into a coherent mental representation. These findings highlight developmental changes in active learning that support flexible reasoning and knowledge building, skills that are crucial for learning and behavior in real-world contexts.